PENINGKATAN KEMAMPUAN BERPIKIR KRITIS BIOLOGI SISWA MELALUI MODEL PROBLEM BASED LEARNING (PBL) DI NEGARA 6 SMA PADANGSIDIMPUAN - Hasanah Nasution; Sahlan Tuah; Nurmaini Ginting (Journal of Natural Sciences, 2020)
This study aims to improve students' critical thinking skills in the field of biology. The analysis technique in this research is critical thinking skills analysis and observation. This type of research is PTC. The results of the evaluation of students' critical thinking skills with learning disabilities were obtained in the first cycle of 51.51% and in the second cycle 84.85% of the 33 students who passed the critical thinking ability test, and there was an increase in the first cycle to II. is 33.34%. %. The results of student observations also experienced an increase in cycle I of 54.17% and cycle II 89.20% an increase of 35.03%, teacher observations in cycle I 67.19%, cycle II 92.19% an increase of 25%.